2016
DOI: 10.1080/17470919.2016.1205131
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI and effective connectivity study investigating miss errors during advice utilization from human and machine agents

Abstract: As society becomes more reliant on machines and automation, understanding how people utilize advice is a necessary endeavor. Our objective was to reveal the underlying neural associations during advice utilization from expert human and machine agents with fMRI and multivariate Granger causality analysis. During an X-ray luggage-screening task, participants accepted or rejected good or bad advice from either the human or machine agent framed as experts with manipulated reliability (high miss rate). We showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…For instance, repeated exposure to robotic actions was shown to increase automatic imitation of these actions to levels comparable to human actions . Moreover, several recent studies on trust during interactions with artificial agents or machines provide compelling first evidence on how expectations and changes in the involvement of the ToM network shape these interactions over time . An exciting opportunity for future research is to study in more detail the dynamic, temporal dimensions of these processes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, repeated exposure to robotic actions was shown to increase automatic imitation of these actions to levels comparable to human actions . Moreover, several recent studies on trust during interactions with artificial agents or machines provide compelling first evidence on how expectations and changes in the involvement of the ToM network shape these interactions over time . An exciting opportunity for future research is to study in more detail the dynamic, temporal dimensions of these processes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, repeated exposure to robotic actions was shown to increase automatic imitation of these actions to levels comparable to human actions 89 . Moreover, several recent studies on trust during interactions with artificial agents or machines provide compelling first evidence on how expectations and changes in the involvement of the ToM network shape these interactions over time 165,169,170 . An exciting opportunity for future research is to study in more detail the dynamic, temporal dimensions of these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, a recent study found that false alarm-prone advice activated different brain regions for a human compared to a machine, including the precuneus, posterior cingulate cortex, and temporoparietal junction ( Goodyear et al, 2016 ). Alternatively, miss-prone advice activated salience and mentalizing brain networks differentially for a human compared to a machine ( Goodyear et al, 2017 ). Another study showed that observing errors for humans and machines results in very similar activation in the medial prefrontal cortex ( Desmet et al, 2014 ), although other work showed that this effect can be moderated by human-likeness of the machine agent ( Krach et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%